A retrospective cohort study about hip luxation in non-ambulatory cerebral palsy patients: The point of no return. (June 2022) - Faccioli, Silvia; Sassi, Silvia; Corradini, Elena; Toni, Francesca; Kaleci, Shaniko; Lombardi, Francesco; Benedetti, Maria Grazia
Purpose: The migration percentage is a widely used criterion for surgery in displaced hips. Literature suggests that no hip can spontaneously improve if the migration percentage exceeds 45%, in a mixed population of cerebral palsy children. The aim of the present article was to identify the point of no return of the migration percentage in a selected sample of non-ambulatory cerebral palsy children, being the most exposed to hip luxation. Methods: This single-center retrospective cohort study included patients with spastic or dyskinetic cerebral palsy, Gross Motor Function Classification System level IV or V, age 0–18, having at least three pelvic radiographies, excluding radiographies relative to hips having previously undergone surgery. The following information was collected: sex, cerebral palsy subtype, Gross Motor Function Classification System level, presence of drug-resistant epilepsy, migration percentage, age at assessment, use of walking or standing assistive devices, previous botulinum injection, oral or intrathecal baclofen, and hip pain. Data were analyzed at the level of the individual hips. Descriptive statistics were presented. Receiver operating characteristic curve analysis was conducted to investigate which value of the migration percentage could be adopted as the "point of no return": that is, the cutoff value beyond which no migration percentage reduction, by more than 5%, could be expected. Results: The optimal cutoff value was identified as migration percentage ≥50%, with a sensitivity of 84.5% and a specificity of 100% (p-value <0.001). Conclusion: Based on the present study, migration percentage ≥50% is the "point of no return" for Gross Motor Function Classification System IV-V cerebral palsy patients, representing the cutoff value beyond which no spontaneous cerebral palsy reduction may be expected, unless addressing surgery. Level of evidence: level II—retrospective study.